Matching Imitative Activity of High-Tech Firms with Entrepreneurial Orientation - Marta Najda-Janoszka (Journal of Entrepreneurship, Management and Innovation)

(untitled)
As pointed by numerous scholars high technology sectors are very apt for studying entrepreneurial activities due to their high levels of innovativeness. However, taking into account the highly dynamic and substantially hostile environment in those sectors, innovation may often not be the best strategic choice for market entry. In fact, the business practice confirms the extensive utilization of imitation strategy by technology entrepreneurs Meanwhile, the literature on entrepreneurship focuses almost exclusively on original innovators, underestimating the importance of imitation in the growth process and indicating shortage of research on imitative activities of entrepreneurs. Therefore this article presents discussion on the applicability of entrepreneurial orientation to imitators from the high-tech industries.